The Effect of Earthquake and Volcanic Eruption to the Nuclear Installation: A Retrospective on 2006 Yogyakarta Earthquake and Merapi Eruption - Yazid, Mochammad; Putri, Khoiria Nur Atika (GMPI Conference Series, 2022)
Earthquake hitting Yogyakarta, Indonesia on May 27th, 2006 that was followed by volcanic eruption of Mount Merapi had been pronounced as one of the most severe natural disasters ever occurred in the national history alongside the Tsunami happened in Aceh, Indonesia on 2004. The earthquake was caused by the activity of Opak faults which is located only ± 7 km away from Kartini nuclear reactor in the Yogyakarta province, Indonesia. This study aims to emphasize on the importance of disaster management mitigation to reduce the potential risk in future possibilities of natural disaster reoccurrence. It was concluded that retrofitting on the nuclear installation setup to withstand earthquake and volcanic eruption along with increasing people awareness and preparedness by arranging trainings on emergency response periodically are of great necessities to reduce the risk in time of disaster. Other than that, this work also described about the community service activities done by Indonesian National Nuclear Agency to help with the community revival post disasters.